Characteristics of Mixed Porus Asphalt with Combination of LDPE, CPO and PEN 60/70 - Meidia Refiyanni; Chaira Chaira (International Journal of Engineering, Science and Information Technology, 2021)
The quality of the road depends on the pavement, drainage conditions, and materials. For this reason, it is necessary to make innovations in improving the quality of road pavement, one of which is increasing the material. There are many types of pavements, one of which is porous asphalt pavement. Porous asphalt has many cavities that is easy for water to pass but has a low stability value with high           permeability. This research will utilize Low Density Poly Ethylene (LDPE), as an additive, CPO, and Pen 60/70 in a porous asphalt mixture. The purpose of this study was to determine the characteristics of the porous asphalt mixture by substituting LDPE and CPO for Pen 60/70. The method used in analyzing the characteristics of the porous asphalt mixture refers to the specifications of the Australis Asphalt Pavement Association (AAPA) (2014), with parameters Camtabro Loss (CL), Asphalt Flow Down (AFD), VIM, stability and flow. The gradation used in this study is an open gradation. This research was started from determining the value of Optimum Asphalt Content (KAO), with two variations, namely Variation 1 (1% LDPE, 10% CPO, 89% pen 60/70), variation 2 (5% LDPE, 10% CPO, 85% Pens 60/70). The KAO value of variation 1 is 5.03% and the second variation is 4.75%. After obtaining the KAO value, LDPE and CPO are substituted. The test results for the porous asphalt mixture for CL values were 34.12% and 27.07%, respectively; AFD value of 0.13% and 0.12%; for the VIM value of 14.90% and 19.03%; stability value 603.24 kg and 603.19 kg; and flow values are 5.03 mm and 4.80 mm. In general, the value obtained from the test meets the required requirements. However, the durability value of the mixture did not meet the requirements, namely 60.15% and 48.22%, with the condition >90%.